Implementation of the performance management policy of the Malawi civil service - Chidwala, Jevas Jafali (My University, 2014)
Implementation of the performance management policy for the Malawi has been held back by a number of factors. There have been indications that suggest that there were some problems resulting in differential implementation of the policy by government’s ministries and departments. In this study the purpose was to find out the factors contributing to this non-implementation of the policy. The research question was; what factors are contributing to the implementation or non-implementation of the performance management policy for the Malawi Civil Service? The study used a qualitative research methodology and questionnaire administered interviews to collect data. The main findings from the study was that implementation of the policy was being hampered because of the complex nature of the public service, absence of follow ups and management support, lack of consultations and motivation factors. The conclusion drawn from the study is that the factors identified are manageable. Therefore, the Department of Public Service and Management and other concerned stakeholders can reflect on the issues revealed by this study, consult widely and put in place necessary mechanism that could ensure successful implementation not only of the performance management but other future polices as well.
Keywords: Performance management; Civil service; Malawi